Respons Bibit Melon (Cucumis melo L.) Varietas TM Gaiya dan Manika terhadap Berbagai Media Persemaian - Shinta Rahmalia; Annisa khoiriyah; Asih Farmia (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2025)
Melon (Cucumis melo L.) was a high-value horticultural commodity with increasing demand in both domestic and international markets. However, melon productivity in Indonesia remained unstable, partly due to low seed quality and the inappropriate selection of seedling media. The seedling stage played a crucial role in determining the success of plant growth in subsequent stages. Therefore, optimal seedling media were required to support the viability, vigor, and early growth of melon seedlings. This study aimed to determine the effects of different seedling media and melon varieties, as well as their interaction, on seed viability, vigor, and early seedling growth. The research was conducted from October 2024 to July 2025 at the Teaching Factory (TEFA) Celeban and the Seed Technology Laboratory of the Agricultural Development Polytechnic of Yogyakarta Magelang. A factorial randomized complete block design (RCBD) with four replications was used. The first factor was seedling media (soil, cocopeat, rice husk charcoal, and vermiculite), and the second was melon varieties (TM Gaiya and Manika). Data were analyzed using ANOVA, DMRT, multiple linear regression, and Pearson correlation for normally distributed data, and Kruskal–Wallis, Mann–Whitney, Generalized Linear Model (GLM), and Kendall Tau-b correlation for non-normal data. Vermiculite showed the best results and was recommended as an effective medium to enhance viability, vigor, and early seedling growth of melon.